Modifiable Risk Factors for Non-Communicable Diseases among Undergraduate Students in Dar es Salaam, Tanzania: A Cross-Sectional Study (Tanzania Medical Journal, 2021)
BackgroundNon-Communicable Diseases (NCDs) are among the global health problems accounting for more than 70% of deaths. Yet, healthcare, workers, university and college students who are key educators to the public about health matters are ironically at high risk for NCDs. We aimed to assess modifiable risk factors for NCDs among undergraduates in Dar es Salaam, Tanzania.MethodsThis was a cross-sectional study among respondents from six universities. The sample was split equally between universities with medical and those without medical courses. Respondents were randomly selected from each of the two clusters of universities. We administered a modified World Health Organization (WHO) STEP-1 questionnaire to collect data on modifiable risk factors for NCDs.ResultsOf the 574 undergraduates studied, 275 (47.9%) were in medical programmes. Among medical students, 262 (95.3%), as compared to 291 (97.3%) of the non-medical undergraduates had at least one NCD modifiable risk factor. While 15 (4.8%) of undergraduates in medical cluster reported consuming heavy alcohol, non-medical undergraduates reporting similar behaviour were 6 (2.3%). The proportion of non-medical undergraduates reporting to lead a sedentary lifestyle was significantly higher, 97 (37.5%), as compared to 82 (31.2%) of their counterparts (p<0.01). Independent of age, marital status and year of study, male undergraduates in non-medical programmes had 16% increased prevalence ratio of modifiable risk factors compared to females, (aPR=1.16, 95%CI: 1.03–1.30).ConclusionsOn one hand, use of tobacco, heavy alcohol consumption and excessive salt intake among undergraduates are low. On the other, the proportions of undergraduates having inadequate fruits and vegetables and physical inactivity are extremely high. Keywords: Non-Communicable Diseases, Modifiable Risk Factors, STEPS Survey, Undergraduates, Tanzania.